Pharmacognostic analyses and antioxidant activity of catharanthus roseus extract obtained from deep eutectic solvent extraction - Nisar, Asma (School of Bioprocess, 2016)
The aim of this research is to develop a green solvent for the extraction of flavonoids from the Catharanthus roseus plant parts and to investigate the pharmacognostic analysis and antioxidant activity from different parts (root, stem,leaves and flower petal) of Catharanthus roseus using DESs extraction. Selection of Catharanthus roseus plant parts for extraction using DESs to be based on the reported chemical constituents. The selection of flavonoids for the antioxidant activity of Catharanthus roseus plant part for this research, not only because of familiarity therewith but also recognition that most medicinal agent of plant origin falls into this category.